Preliminary Design Investigation of Dual Stator HE FSM using Segmental Rotor - Ali, Hassan; Sulaiman, Erwan; Omar, Zamri; F. Omar, M; Amin, Faisal; Khalidah Rahimi, S (International Journal of Engineering and Technology, 2018)
ToÂ dropÂ theÂ effectÂ ofÂ airÂ transportationÂ onÂ the atmosphereÂ asÂ wellÂ asÂ toÂ advanceÂ fuelÂ productivityÂ more-electric aircraft (MEA) architectures is a well-known approach. As the electrical machines are competent to deliver higher torque densities and are foremost for the viability of electrical driving force for aircraft applications. For these reasons a new category of machine has been familiar and published in last decade known as flux switching machine (FSM).Â FSMs comprises all excitation sources on stator side without winding robust rotor structure. Additionally, FSMs are classified into three types such as permanent magnet (PM) FSMs, field excitation (FE) FSMs and hybrid excitation (HE) FSMs. PM FSM and FE FSM useÂ PMÂ andÂ FEÂ coilÂ forÂ theirÂ excitationÂ sourcesÂ respectively, whereas both PM and FE coil areÂ used in HE-FSM for excitation. Afterwards, HE FSMs have shown higher torque to weight ratios with higher efficiency during research in the last decade. Yet, in existing structures of HE FSMs, there is flux cancellation between the fluxes of PMs and FE coil which causes to reduce the performance of machines. Hence, in this paper, a novel structure of dual stator (DS) HE FSM with segmented rotor has been proposed and analyzed.Â The main reason of dual stator is to make the separate flow fluxes in HE machines to avoid cancellations. The proposed novel DS HE FSM has a simple structure using dual stators to endorse separate dual excitations to be used in fault conditions. The proposed structure has been analyzed using commercial 2D FEA package, JMAG-designer. Initially, this paper presents the coil test analysis of proposed DS HE FSM to confirm the working principle. Besides, performance analysis has been carried out at no load and load conditions.Â Â